Step-by-step explanation:
(x^4)^3=(x^3)^4 , true
=> x^(4×3) = x^(3×4) = x^12
13^4 x 13^7= (13^4)^7, false
13^(4+7) = 13^11
(13^4)^7 = 13^(4×7) = 13^28
y^5 x y^0/y^3=(y^2)^1 , true
y^5 x y^0/y^3 = y^(5+0-3) = y^2
(y^2)^1 = y^(2×1) = y^2
q^0 x q^5/q^2=(q^3)^2/q^3, true
q^0 x q^5/q^2= q^(0+5-2)= q^3
(q^3)^2/q^3 = q^(3×2-3) = q^3
Answer:
8
Step-by-step explanation:
(10-4)+20/20
6+20/10
6+2
8
George can feed up to 6 people because there are 12 pieces of sandwich and each person eats 2
Answer:
335 and 289
Step-by-step explanation:
335 is rounded to 300 and 289 is rounded to 300
Answer : The correct option is (A) 68.
Step-by-step explanation :
As we are given that:
LN = 6x - 5
LM = x + 7
MN = 3x + 20
Now we have to determine the value of MN.
According to the question:
LN = LM + MN
Now putting all the given values in this expression, we get:
6x - 5 = (x + 7) + (3x + 20)
6x - 5 = 4x + 27
6x - 4x = 27 + 5
2x = 32
x = 16
The value of MN = 3x + 20 = 3(16) + 20 = 48 + 20 = 68
Therefore, the value of MN is 68.